Chronic exercise increases plasma brain-derived neurotrophic factor levels, pancreatic islet size, and insulin tolerance in a TrkB-dependent manner. - Alberto Jiménez-Maldonado; Elena Roces de Álvarez-Buylla; Sergio Montero; Valery Melnikov; Elena Castro-Rodríguez; Armando Gamboa-Domínguez; Alejandrina Rodríguez-Hernández; Mónica Lemus; Jesús Muñiz Murguía (PLoS ONE)
Background Physical exercise improves glucose metabolism and insulin sensitivity. Brain-derived neurotrophic factor (BDNF) enhances insulin activity in diabetic rodents. Because physical exercise modifies BDNF production, this study aimed to investigate the effects of chronic exercise on plasma BDNF levels and the possible effects on insulin tolerance modification in healthy rats. Methods Wistar rats were divided into five groups: control (sedentary, C); moderate- intensity training (MIT); MIT plus K252A TrkB blocker (MITK); high-intensity training (HIT); and HIT plus K252a (HITK). Training comprised 8 weeks of treadmill running. Plasma BDNF levels (ELISA assay), glucose tolerance, insulin tolerance, and immunohistochemistry for insulin and the pancreatic islet area were evaluated in all groups. In addition, Bdnf mRNA expression in the skeletal muscle was measured. Principal findings Chronic treadmill exercise significantly increased plasma BDNF levels and insulin tolerance, and both effects were attenuated by TrkB blocking. In the MIT and HIT groups, a significant TrkB-dependent pancreatic islet enlargement was observed. MIT rats exhibited increased liver glycogen levels following insulin administration in a TrkB-independent manner. Conclusions/significance Chronic physical exercise exerted remarkable effects on insulin regulation by inducing significant increases in the pancreatic islet size and insulin sensitivity in a TrkB-dependent manner. A threshold for the induction of BNDF in response to physical exercise exists in certain muscle groups. To the best of our knowledge, these are the first results to reveal a role for TrkB in the chronic exercise-mediated insulin regulation in healthy rats.